Nanette Streicher, geb. Stein: Nach einem alten Portrait - Käseberg, Hugo, 1847-1893 (engraver):::Creator::::::::::::; Krones, Ludwig, 1785-1830 (artist):::Contributor::::::::::::; Oertel, Kaspar Erhardt, 1840-after 1901 (engraver):::Creator::::::::::::
Portrait engraving of Nanette Streicher by Hugo Käseberg and Kaspar Oertel based on the painting by Ludwig Krones.